2000
DOI: 10.1046/j.1469-7580.2000.19720157.x
|View full text |Cite
|
Sign up to set email alerts
|

Regression of blood vessels in the ventral velum of Xenopus laevis Daudin during metamorphosis: light microscopic and transmission electron microscopic study

Abstract: Structural changes of the ventral velum of Xenopus laevis tadpoles from late prometamorphosis (stage 58) to the height of metamorphic climax (stage 62) were examined by light and transmission electron microscopy. Special emphasis was given to the blood vessel regression. Early changes of velar capillaries were formation of luminal and abluminal endothelial cell processes, vacuolation, and cytoplasmic and nuclear chromatin condensation. At the height of metamorphic climax, transmission electron microsco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 28 publications
2
7
0
Order By: Relevance
“…1e) or in a multifocal manner (Fig. 1f,g), similar to the process of vascular obliteration observed by others (Bartel and Lametschwandtner, 2000). By means of this "fold" mechanism, the branching angle decreases and the bifurcation point moves either upstream (in arteries) or downstream (in veins).…”
Section: Morphology and Time Seriessupporting
confidence: 80%
“…1e) or in a multifocal manner (Fig. 1f,g), similar to the process of vascular obliteration observed by others (Bartel and Lametschwandtner, 2000). By means of this "fold" mechanism, the branching angle decreases and the bifurcation point moves either upstream (in arteries) or downstream (in veins).…”
Section: Morphology and Time Seriessupporting
confidence: 80%
“…To determine whether apoptosis was occurring equally in the GFP and XR11 transgenic tadpoles, we focused on the ventral velum, a portion of the larval filter feeding apparatus that has a chevron shape in cross section before it dissociates through apoptosis during metamorphosis [45]. As shown in Figure 3K–R, TUNEL-positive nuclei, which are rare in the velums in the absence of T 3 , were prevalent in the velums of both T 3 -treated GFP and XR11 transgenic tadpoles.…”
Section: Resultsmentioning
confidence: 99%
“…In studies of cyclic angiogenesis and blood vessel regression in the ovary, in 1996, Modlich et al [133] found that capillary endothelial cells detached from the basement membrane singly or in sheets, and most endothelial cells became detached before undergoing apoptosis. Bartel and Lametschwandtner [134], studying regression of capillaries in tadpole epithelium, found that endothelial cells bulged into the lumen, almost plugging the vessel. Many endothelial cells were apoptotic.…”
Section: Endothelial Cell Destructionmentioning
confidence: 99%